Answer:
the answer is b because yeah also thats a translation not a rotation
Answer:
863.95
Step-by-step explanation:
1010×0.94=949.4
949.4×0.91=863.954
863.95
Answer:
64°
Step-by-step explanation:
In circle with center P, AD is diameter.
![\therefore m\angle DPE + m\angle APE = 180\degree \\\therefore (33k-9)\degree + 90\degree = 180\degree \\\therefore (33k-9)\degree = 180\degree -90\degree \\\therefore (33k-9)\degree = 90\degree \\\therefore 33k-9 = 90\\\therefore 33k= 90+9\\\therefore 33k= 99\\\therefore k= \frac{99}{33}\\\therefore k=3\\ m\angle CPD = (20k +4)\degree \\\therefore m\angle CPD = (20\times 3 +4)\degree \\\therefore m\angle CPD =(60+4)\degree \\\therefore m\angle CPD =64\degree \\m\overset {\frown}{CD} = m\angle CPD\\\therefore m\overset {\frown}{CD} = 64\degree](https://tex.z-dn.net/?f=%20%5Ctherefore%20m%5Cangle%20DPE%20%2B%20m%5Cangle%20APE%20%3D%20180%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%20%2833k-9%29%5Cdegree%20%2B%2090%5Cdegree%20%3D%20180%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%2833k-9%29%5Cdegree%20%20%3D%20180%5Cdegree%20-90%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%20%2833k-9%29%5Cdegree%20%20%3D%2090%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%2033k-9%20%3D%2090%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%2033k%3D%2090%2B9%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%2033k%3D%2099%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%20k%3D%20%5Cfrac%7B99%7D%7B33%7D%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20%20k%3D3%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3E%20m%5Cangle%20CPD%20%3D%20%2820k%20%2B4%29%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20m%5Cangle%20CPD%20%3D%20%2820%5Ctimes%203%20%2B4%29%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20m%5Cangle%20CPD%20%3D%2860%2B4%29%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20m%5Cangle%20CPD%20%3D64%5Cdegree%20%5C%5C%3C%2Fp%3E%3Cp%3E%3C%2Fp%3E%3Cp%3Em%5Coverset%20%7B%5Cfrown%7D%7BCD%7D%20%3D%20m%5Cangle%20CPD%5C%5C%3C%2Fp%3E%3Cp%3E%5Ctherefore%20m%5Coverset%20%7B%5Cfrown%7D%7BCD%7D%20%3D%2064%5Cdegree%20%20%3C%2Fp%3E%3Cp%3E)
<span>y=-4/x+1 is ambiguous, since it's not immediately clear whether you meant
-4
y = -4/x + 1 or y = ---------
x+1
I'm going to assume that the latter is what you meant.
1. Interchange x and y, obtaining:
-4
x = --------
y+1
2. Solve this for y, obtaining y+1 = -4/x, or xy + x = -4, or
-x - 4
xy = -x-4, or y = ---------
x
-1 -1 4
3. Replace y with f (x): f (x) = -1 - -----
x
This last result has the correct form.</span>
I'm assuming your function is f(x) = -9^(x+1)
So we just have to plug in and see if the function is true.
1) -9^(0+1) = -9^1 = -9
YES
2) -9^(1+1) = -9^2 = -81
NO
3) -9^(-1+1) = -9^0 = -1
YES